Diversity of cystic fibrosis chronic rhinosinusitis microbiota correlates with different pathogen dominance - Lucas, Sarah K.; Feddema, Erin; Boyer, Holly C.; Hunter, Ryan C. (Journal of cystic fibrosis, 2021)
•16S rRNA gene sequencing and amplicon sequence variant (ASV) analysis reveals an unrealized diversity of CRS microbiota not captured by clinical culture.•CF-CRS microbiota dominated by Staphylococcus aureus harbor significantly more bacterial diversity relative to those dominated by Pseudomonas aeruginosa.•Sinus bacterial diversity does not correlate with CRS co-morbidities.•CF-CRS microbiology mirrors bacterial community dynamics in the CF lung. Chronic rhinosinusitis (CRS) affects nearly all individuals with cystic fibrosis (CF) and is thought to serve as a reservoir for microbiota that subsequently colonize the lung. To better understand the microbial ecology of CRS, we generated a 16S rRNA gene sequencing profile of sinus mucus from CF-CRS patients. We show that CF-CRS sinuses harbor bacterial diversity not entirely captured by clinical culture. Culture data consistently identified the dominant organism in most patients, though lower abundance bacteria were not always identified. We also demonstrate that bacterial communities dominated by Staphylococcus spp. were significantly more diverse compared to those dominated by Pseudomonas spp. Diversity was not significantly associated with clinical factors or patient age, however, younger subjects yielded a much wider range of bacterial diversity. These data mirror bacterial community dynamics in the lung and provide additional insight into the role of sinus microbiota in chronic airway disease progression.